2019
DOI: 10.1021/acs.chemrev.8b00732
|View full text |Cite
|
Sign up to set email alerts
|

Halide Photoredox Chemistry

Abstract: Halide photoredox chemistry is of both practical and fundamental interest. Practical applications have largely focused on solar energy conversion with hydrogen gas, through HX splitting, and electrical power generation, in regenerative photoelectrochemical and photovoltaic cells. On a more fundamental level, halide photoredox chemistry provides a unique means to generate and characterize one electron transfer chemistry that is intimately coupled with X−X bond-breaking and -forming reactivity. This review aims … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
142
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 157 publications
(158 citation statements)
references
References 512 publications
5
142
0
Order By: Relevance
“…This has been shown to enhance the formation of ion pairs between cationic ruthenium polypyridyl compounds and anions in acetonitrile (CH 3 CN). 23,44,[55][56][57] The four ruthenium compounds utilized in this study follow the common structure of [Ru(tmam)(LL) 2 ](PF 6 ) 4 , where LL was 4,4 0dimethoxy-2,2 0 -bipyridine (OMe), 4,4 0 -di-tert-butyl-2,2 0 -bipyridine (Dtb), 2,2 0 -bipyridine (Bpy), and 2,2 0 -bipyrazine (Bpz). Herein, the compounds will be denoted Ru-LL where LL is the short name of the derivatized bipyridine or bipyrazine ligand (Scheme 2B).…”
Section: Ion Pair Formationmentioning
confidence: 99%
“…This has been shown to enhance the formation of ion pairs between cationic ruthenium polypyridyl compounds and anions in acetonitrile (CH 3 CN). 23,44,[55][56][57] The four ruthenium compounds utilized in this study follow the common structure of [Ru(tmam)(LL) 2 ](PF 6 ) 4 , where LL was 4,4 0dimethoxy-2,2 0 -bipyridine (OMe), 4,4 0 -di-tert-butyl-2,2 0 -bipyridine (Dtb), 2,2 0 -bipyridine (Bpy), and 2,2 0 -bipyrazine (Bpz). Herein, the compounds will be denoted Ru-LL where LL is the short name of the derivatized bipyridine or bipyrazine ligand (Scheme 2B).…”
Section: Ion Pair Formationmentioning
confidence: 99%
“…Following our success with 34, we then applied this cascade CC bond cleavage and oxygenation to the poly-ε-caprolactoneblock-polyethyleneglycol-block-poly-ε-caprolactone (PCL-PEG-PCL) triblock co-polymer (35). The reaction proceeded smoothly with complete polymer transformation within 2 days under ambient conditions, with formic acid as the major product ( Figure 5, Entry 2).…”
Section: Cascade Cc Cleavage For Sustainable Energy and Environmentamentioning
confidence: 99%
“…This concept had been pioneered by Meyer and co-workers, who demonstrated its potential for chloride [25] and benzyl alcohol oxidation with simultaneous H 2 evolution. [26] Others, including Sun and co-workers, [27][28][29][30] Meyer and co-workers, [31][32][33][34][35] Berlinguette and co-workers, [36][37][38] Reisner and co-workers, [14,[39][40][41] and Lei and co-workers, [42][43][44] have subsequently shown that the gap between AP and radical catalysis can potentially be bridged via the valorization of biomass, functionalization of amines, oxidation of other halides, photo-electrochemical reduction of CO 2 , and even photoreforming of plastics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides alcohol oxidation, T. J. Meyer, G. J. Meyer, and their coworkers have also been investigating halide oxidation reactions as substitutes for water oxidation in a PEC . Water oxidation is a four‐electron process and poses many kinetic challenges, whereas halide oxidation reactions are just two‐electron processes and should in principle be faster.…”
Section: Pecs For Catalytic Synthesesmentioning
confidence: 99%